SHIPPING OIL FUEL BY GROUP PELANGSIR AS A COMMUNITY LIVELIHOOD MUARA TEWEH - Edwin Rionaldy (JURNAL SOCIUS, 2022)
The rise of slashing as an alternative to profitable work is carried out by the middle to lower class people of Muara Teweh. Passing is done because of the lack of job opportunities so that the community is a source of livelihood. This work for some people in Muara Teweh is only used as a side job because the income from the main job is not enough to meet their daily needs, the purpose of this study is to describe the actions of the BBM slasher, to describe the function of the BBM slasher community group, to analyze the consequences received or experienced by the slasher with the presence of slimming activity. The method used in this research is a qualitative method. Data source selected by purposive sampling. The data collection was carried out by the technique of observation, interview and documentation. Technical data analysis using qualitative analysis with data reduction steps, data presentation and  drawing conclusions, shunts The results of the study illustrate the prevalence of  be used as a side job, take advantage of living conditions,  provide a lot of profit and little capital, the function of the curator group  is of two kinds, namely the function of the group for individuals as a means of  establish social relations and group functions for the community as  social control, the positive impact is for people who are far away facilitate the distribution of fuel to villages, create new job opportunities  The negative impact is for the shunters themselves, such as competition between fellow  pangsirs, conflicts among shunters and the general public who are currently experiencing  queuing for fuel at gas stations, raiding smugglers' losses, paying fines, and  confiscation of goods.